An improved DNB-type critical heat flux prediction model for flow boiling at subcritical pressures in vertical rifled tube. (April 2019) - Xie, Haiyan; Yang, Dong; Wang, Wenyu; Wan, Li; Li, Chunmei
Highlights: A new DNB-type CHF prediction model of flow boiling in rifled tube at low qualities was established. A new αb correlation was proposed based on a large number of CHF experimental data. The present model was verified by the CHF look-up values and CHF experimental values. Three classic CHF prediction models and the present CHF model were evaluated. With the increase of vapor quality, the influence of pressure and mass flux on CHF weakened. Abstract: Based on the near-wall bubble coalescence model and the structural characteristics of the rifled tube, improvements and optimization of the model for rifled tube were conducted. DNB-type CHF phenomenon in the rifled tube under subcritical and near-critical pressures was investigated by numerical calculation. A new CHF prediction model of flow boiling in rifled tube with low qualities was established and compiled by FORTRAN language. The model used the Staub model which considering the influence of the bubble contact angle to calculate the bubble detachment diameter. The surface friction coefficient of the rifled tube was calculated by the classical Kohler and Kastner formula. And a new critical void fraction of the wall bubbly layer αb correlation was proposed based on a large number of CHF experimental data. The present model was verified by the CHF look-up values and CHF experimental values. Based on the CHF experimental data of the rifled tube, three classic CHF prediction models and the present CHF model were evaluated, and it was found that the present modified CHF model has the highest prediction accuracy for the rifled tube, which is the best agreement with the experimental values, indicating that the present model is appropriate for DNB-type CHF prediction of the rifled tube. In this paper, the effects of pressure, mass flux and inlet fluid subcooled enthalpy on CHF were studied. It was found that, the effect of pressure and mass flux on CHF is obvious in the low quality region, with the increase of vapor quality, the influence of pressure and mass flux on CHF weakens.